Association of Preexisting Asthma and Other Allergic Diseases With Mortality in COVID-19 Patients: A Systematic Review and Meta-Analysis - Wu, Xianbo; Xu, Yihua; Jin, Lina; Wang, Xiaoou; Zhu, Haiyan; Xie, Yiqiang (Frontiers in Medicine, 2021)
Background: Respiratory viruses are known to contribute to asthma exacerbations. A meta-analysis of three studies reported no association between coronavirus disease 2019 (COVID-19) mortality and preexisting asthma. This study aimed to investigate the mortality of patients with COVID-19 in relation to preexisting asthma and other allergic diseases associated with changes in respiratory function. Methods: PubMed, Embase, and the Cochrane Library were queried for papers published up to April 9, 2021: (1) population: patients who tested positive for SARS-CoV-2 according to the WHO guidelines; (2) exposure: preexisting asthma or allergic rhinitis; (3) outcomes: mortality, ICU admission, and/or hospitalization; and (4) language: English. For studies that reported adjusted models, the most adjusted model was used for this meta-analysis; otherwise, unadjusted results were used. Results: Twenty-four studies (1,169,441 patients) were included in this meta-analysis. Patients who died of COVID-19 were not more likely to have preexisting asthma (OR = 0.95, 95%CI: 0.78–1.15, P = 0.602; I2 = 63.5%, Pheterogeneity < 0.001). Patients with COVID-19 and admitted to the ICU (OR = 1.17, 95%CI: 0.81–1.68, P = 0.407; I2 = 91.1%, Pheterogeneity = 0.407), or hospitalized (OR = 0.91, 95%CI: 0.76–1.10, P = 0.338; I2 = 79.1%, Pheterogeneity < 0.001) were not more likely to have preexisting asthma. The results for mortality and hospitalization remained non-significant when considering the adjusted and unadjusted models separately. The results from the sensitivity analyses were consistent with the primary analyses, suggesting the robustness of our results. Conclusion: This meta-analysis suggests that the patients who died from COVID-19, were admitted to the ICU, or hospitalized were not more likely to have asthma.